KEPUASAN PELANGGAN TERHADAP JASA PENGIRIMAN BARANG MENGGUNAKAN METODE ALGORITMA C4.5 - Nurul Azwanti; Sri Tria Siska; Liga Mayola (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Currently shipping services are needed by the community to make it easier to move between cities and transport products or trade goods. PT. Kerabat Jasa Antar is a provider of goods delivery services based in the Batam area and already has many customers. Quality of service is the most important factor to win the competition between shipping services. Goods delivery service providers must give the best to their customers in order to survive. Therefore, it is necessary to analyze customer satisfaction to see whether the customer is satisfied or not with the services provided. The research method uses interview techniques and distributes questionnaires and studies literature related to research. The C4.5 algorithm is a data mining method that is capable of producing rules to view the results of customer satisfaction data processing. The results of the rules that are formed are 4 rules with the attributes that affect are Security, Timeliness and Service. The first rule is if the security is not safe, then the customer is not satisfied, the next rule is if the security is safe, on time is not and the service is not good then the customer is not satisfied. Testing was carried out using the Weka application where the decision tree formed produced the same rules as the analysis that had been carried out. The results of this study are expected to be a consideration for companies to improve their performance in order to retain their customers.